2014
DOI: 10.4236/ojcd.2014.43019
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Calcaneal Comminuted Intrarticular Fractures: Long-Term Follow-Up

Abstract: There is a controversy whether the comminuted calcaneal fractures should benefit more from conservative or from surgical treatment. Aiming to contribute to this unsolved clinical question we reviewed the long-term outcome (up to 96 months) of in 44 patients (mean age 35 years) with 47 calcaneal fractures who were treated surgically. In these patients open reduction and internal fixation were performed using a calcaneal reconstruction plate. The functional outcome was measured according to the Rowe Score and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The mean preoperative Bohler angle was 12.6 0 and immediate postoperative was 28 0 and at final follow up was 27.6 0 and it was maintained in the normal range (20° to 40°) in all the patients which is a better result than Santosha et al (22) where the angle was restored and maintained only in 25 (83.3%) feet after 24 months of follow-up. Haddad et al (25) noted that restoration of Bohler's angle in 74% of calcaneum, while 86.6% of calcaneal restoration was reported in a study conducted by Jain et al (26) who found that the mean Bohler's angle improved from preoperative 4.15° to immediate postoperative 27.69° which was decreased to 25.47° at final follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…The mean preoperative Bohler angle was 12.6 0 and immediate postoperative was 28 0 and at final follow up was 27.6 0 and it was maintained in the normal range (20° to 40°) in all the patients which is a better result than Santosha et al (22) where the angle was restored and maintained only in 25 (83.3%) feet after 24 months of follow-up. Haddad et al (25) noted that restoration of Bohler's angle in 74% of calcaneum, while 86.6% of calcaneal restoration was reported in a study conducted by Jain et al (26) who found that the mean Bohler's angle improved from preoperative 4.15° to immediate postoperative 27.69° which was decreased to 25.47° at final follow-up.…”
Section: Discussionmentioning
confidence: 95%